INTERNATIONAL LEGAL REGULATION OF TEMPORARY LOAN OF CULTURAL PROPERTY: CONTROVERSIAL ISSUES - D. A. LABUT (Московский журнал международного права, 2018)
INTRODUCTION. One of the main priorities of international cooperation regarding cultural property is providing access to such cultural objects both for the citizens of the state where the objects are normally located and for the whole international community. This aim may be achieved by active international loans, which often presume temporary export of cultural property to the territory of a foreign state. The lack of legal guarantees regarding its timely and safe return to the state of origin creates anxiety and unwillingness of states to send away their cultural heritage and thus hampers international cultural exchange. Closely related to this matter is the question of international legal regulation of the immunity of such cultural property, temporary present on the territory of another state, from suit and seizure.MATERIALS AND METHODS. The material for the study was the applicable provisions of international treaties, in particular the 2004 UN Convention on Jurisdictional Immunities of States and Their Property, 2004, the practice of international judicial bodies, as well as the works of Russian and foreign researchers in the field of international legal bases for the protection and circulation of cultural property. The methodological basis of the research consists of general theoretical methods (dialectical method, comparative method, analysis and synthesis, induction and deduction) as well as special legal methods (historical-legal, formal-legal, comparative-legal and other methods).RESEARCH RESULTS. At the moment, the international legal regulation of the matter seems insufficient: the 2004 UN Convention on Jurisdictional Immunities of States and Their Property, containing potentially applicable provisions, has not yet entered into force, and there is no perspective of any satisfactory regulation in the form of a treaty in the nearest future. However, the author states the formation of a relatively young rule of customary international law on the immunity of cultural property, which is, however, strictly limited by various conditions. This immunity does not extend, for example, to stolen or illegally exported objects for which there are obligations of states for their restitution (return) in accordance with existing international treaties. In addition, the immunity from coercive measures does not exempt from jurisdiction, and the temporary presence of cultural values of one state in the territory of another one may serve as the basis for the notification of a claim against the first country by the courts of the second one.DISCUSSION AND CONCLUSION. In this article the attention is focused on the fact that the immunity of cultural values is a condition for an active international exchange of them, and, consequently, is a pledge for the further development of international cultural cooperation and scientific research. Uncertainty in this matter is a source of numerous doctrinal disputes and practical problems. According to the results of the research, the author makes a conclusion, that the situation calls for further progressive development and codification of international law in this area, including the creation of detailed and specific norms regarding the immunity of cultural property temporary on loan for cultural, scientific and educational purposes, which will encourage international loans of cultural objects and promotion of intercultural cooperation.